CAME 56 - Comparsion of thermoelastic results in two types of functionally graded brake disks - Sahari, B.B.; Shahzamanian, M.M.; Bayat, M. (2010)
Thermoelastic simulation of functionally graded (FG) brake disk using finite element (FE) ANSYS software is performed. The material properties of two types of FG brake disks are assumed to vary in radial and thickness direction according to a power law distribution. The brake disks are in contact with one hollow pure pad disk. Dry contact friction is considered as the heat source. The proper thicknesses of pad disks are found to have full-contact status. The behavior of thermoelastic results for thickness and radial FG brake disks are compared. The results show that the behavior of temperature and vertical displacement in these two types of FG brake disks are the same. On the other hand, the variations of radial displacements for different grading indices n are not the same. The behaviors of other results are quite the same. It can be concluded that the variation direction of material properties in FG brake disk can affect the results. Keywords: functionally graded material, finite element method, brake disk, thermoelastic.